PROBLEMS IN THE DEVELOPMENT OF REMOTE BANKING SERVICES IN COMMERCIAL BANKS OF UZBEKISTAN - Prof. Suyunov Dilmurod Kholmurodovich; Kaytarov Vokhid (Scholar Express Journals, 2023)
The article lists internal and external factors that affect the development of remote banking services. The article covers problems in the development of remote banking services and presents author's approaches to their elimination.
Keywords: Remote banking services; Internet site; risk; banking technologies